RISK FACTORS FOR ACUTE DIARRHEAL DISEASES IN CHILDREN TREATED AT THE CUANZA NORTE PROVINCIAL MATERNAL AND CHILD HOSPITAL FROM MARCH TO OCTOBER 2024 - Pilarte António, Sara; de Fátima João Domingos Manuel, Neusa (Health and Society, 2025)
Acute diarrheal diseases represent one of the main causes of infant morbidity and mortality in developing countries, especially in regions with poor sanitation and limited access to potable water. This study aimed to identify the risk factors and prevalence of acute diarrheal diseases in children treated at the Cuanza Norte Provincial Maternal and Child Hospital between March and October 2024, also analyzing the prevention measures adopted. A cross-sectional descriptive study with a quantitative-qualitative approach was conducted, involving a sample of 505 children. Data collection was carried out using a data collection form. Of the 505 cases analyzed, 35 were positive for acute diarrheal diseases. The majority were female, with 22 cases (63%). The most affected age group was 1 to 5 years, with 16 cases (46%). The neighborhood with the highest incidence was Bairro Posse, with 13 cases (37%). Escherichia coli was the most prevalent etiological agent, with 20 cases (57%), while Giardia lamblia had the lowest occurrence (9%). The main risk factor identified was the consumption of contaminated water (43%), followed by insufficient breastfeeding (23%). The results show that acute diarrheal diseases are still a relevant problem in the local child population, being strongly related to environmental and behavioral factors. Investing in basic sanitation, water treatment, promoting breastfeeding, and educational campaigns are essential measures to reduce the incidence of these diseases.